2016
DOI: 10.1007/s10841-015-9842-x
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of invaded Cape Floristic Region riparian systems leads to a recovery in foliage-active arthropod alpha- and beta-diversity

Abstract: AcknowledgmentsThanks to Marno Fourie and Oliver Kambaj for field assistance and reviewers for helpful suggestions to improve this manuscript. We thank private landowners and CapeNature for access to field sites (permit number: AAA008-00027-0028). This study was funded by the DST/NRF Centre of Excellence in Tree Health Biotechnology. Conflict of Interest: The authors declare that they have no conflict of interest. AbstractThe Cape Floristic Region of South Africa is a global biodiversity hotspot threatened by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 64 publications
(61 reference statements)
1
7
0
Order By: Relevance
“…Moreover, our results show that, in the Iberian Peninsula, the abundance and species richness of feeding guilds tended to be significantly reduced by the presence of C. edulis. These results agree with previous research which found that introduced plants can alter the trophic diversity in invaded areas (Procheş et al 2008;Moroń et al 2009;Maoela et al 2016;McCary et al 2016;Rodríguez et al 2020). The reduction in the abundance of herbivores, omnivores and predators in the areas invaded by C. edulis compared with those without C. edulis is striking.…”
Section: Trophic and Taxonomic Groupssupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, our results show that, in the Iberian Peninsula, the abundance and species richness of feeding guilds tended to be significantly reduced by the presence of C. edulis. These results agree with previous research which found that introduced plants can alter the trophic diversity in invaded areas (Procheş et al 2008;Moroń et al 2009;Maoela et al 2016;McCary et al 2016;Rodríguez et al 2020). The reduction in the abundance of herbivores, omnivores and predators in the areas invaded by C. edulis compared with those without C. edulis is striking.…”
Section: Trophic and Taxonomic Groupssupporting
confidence: 92%
“…However, in the Iberian Peninsula, we found that the presence of C. edulis significantly reduced only the abundance, while it increased the values of the Shannon, Simpson and Pielou evenness indices. Some authors have noted that introduced plants may induce a negative effect on the arthropod communities (Procheş et al 2008;Dibble et al 2013;Van der Colff et al 2015;Maoela et al 2016). However, this does not seem to be the case for C. edulis (Rodríguez et al 2019).…”
Section: Alpha-diversitymentioning
confidence: 99%
“…In this sense, leaf N content is an important driver of arthropod population dynamics in A. mearnsii stands (Maoela et al 2016a). Nevertheless, arthropod assemblages in the native community can be progressively recovered after the removal of the exotic (Maoela et al 2016b). On the other hand, Eichhorn et al (2011) indicated that the artificial damage induced to the leaves of A. dealbata activated the production of extra-floral nectaries.…”
Section: Macrofaunamentioning
confidence: 99%
“…For example, in the hyperdiverse fynbos biome of South Africa, the removal of invasive A. mearnsii trees from riparian zones, and the subsequent recovery of native plant diversity, helped to recover both alpha and beta arthropod diversity (Maoela et al , 2016). However, as recently shown, pathogen accumulation on a highly invasive grass in the US may also help to significantly reduce the fitness of invasive populations in the future (Stricker et al , 2016).…”
Section: Implications For Biological Control Of Non-native Treesmentioning
confidence: 99%
“…The physical removal of invasive trees and the active rehabilitation of natural biotic communities have been suggested as a more effective invasion management strategy than relying on enemy accumulation over time ( Parker et al , 2006 ). For example, in the hyperdiverse fynbos biome of South Africa, the removal of invasive A. mearnsii trees from riparian zones, and the subsequent recovery of native plant diversity, helped to recover both alpha and beta arthropod diversity ( Maoela et al , 2016 ). However, as recently shown, pathogen accumulation on a highly invasive grass in the US may also help to significantly reduce the fitness of invasive populations in the future ( Stricker et al , 2016 ).…”
Section: Implications For Biological Control Of Non-native Treesmentioning
confidence: 99%